Factors Influencing Poor Postnatal Care in Sangihe Regency - Jelita Siska Herlina Hinonaung; Astri Juwita Mahihody; Grace Angel Wuaten (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2021)
Postpartum mothers from the first day of childbirth up to six weeks will undergo changes both physically and psychologically making intensive care indispensable. Conditions in which the postpartum mother does not get the correct and timely postnatal care lead to postpartum complications that can cause death. The objective of the study is to identify factors related to poor postnatal care in Sangihe Regency, North Sulawesi. This research was a correlation cross-sectional study. The population was postpartum mothers in the working area of The Kuma Health Center of Sangihe Regency. In this study, researchers sampled 62 respondents. The variables included age, culture, mode of delivery, support, and knowledge. The relationship between age, culture, mode of delivery, support, and knowledge with poor postnatal care was measured less using the chi-square test. In contrast, the determinants of poor postnatal care were identified employing logistics regression. The results showed that factors influencing poor postnatal care were age, culture, mode of delivery, support, and knowledge. Mode of delivery was discovered as the most dominant variable influencing poor postnatal care. This research concluded that age, culture, mode of delivery, support and knowledge had a correlation with poor postnatal care, and the most dominant variable was the mode of delivery. Researcher hopes that these findings could help health workers and local governments to direct appropriate postpartum care, especially other postnatal care requiring further research.